Success of External Cephalic Version and Frequency of Cesarean Section in Patients (Medical Forum Monthly, 2024)
Objective: Frequency of success in patients undergoing external cephalic version and assesses rate of C-section after successful external cephalic version. Study Design: Descriptive Case Series. Place and Duration of Study: This study was conducted at the Department of Obstetrics & Gynaecology, M. Islam Medical College Gujranwala from October 2018 to March 2019. Materials and Methods: Seventy patients with gestational ages between 34 to 40 weeks were included. Patients underwent external cephalic version in labour room by a single consultant. Results: 58% patients underwent successful external cephalic version and 41% patient’s external cephalic version were not successful. Among patients undergoing successful external cephalic version, 39% were delivered by cesarean section and 61% were delivered by spontaneous vaginal delivery. There was no maternal and fetal complication noted. Conclusion: External cephalic version is a safe and effective treatment modality with high rate of success and also effective for reducing the rate of cesarean sections.